Outcome of late preterm infants and the factors associated with neonatal intensive care admission - Alam, M. Mahfooz; Alam, Shahzad; Mazahir, Rufaida (International Journal of Research in Medical Sciences, 2023)
Background: Infants born between 34 0/7 and 36 6/7 weeks of gestation are referred to as late-preterm infants (LPI). The study’s objective was to examine the prevalence and course of LPI at our institution. Methods: This single-center prospective observational study was conducted at the level 3 NICU from June 2018 to June 2019 and included LPIs born in the hospital. Both the prevalence of LPI and the reasons for premature births were evaluated. Infants were observed until discharge for complications and outcomes (mortality and NICU admission). The risk factors associated with NICU admission were analyzed using multivariate logistic regression analysis. Results: LPI constitutes 2.94% of all live births and 40.45% of total preterm births. Pre-eclampsia (15.1%) and premature membrane rupture (9.4%) were the two main causes of preterm birth, while the majority of mothers (37.7%) experienced spontaneous labor. A total of 55 (51.9%) babies developed complications, with respiratory distress (33.9%) being the most common. Three infants died, and 65 infants needed admission to the NICU. NICU hospitalization was independently associated with the existence of maternal risk factors, gestational age of 35 weeks, the requirement for resuscitation, and children whose weight was out of proportion to their gestational age. Conclusions: LPIs account for a large proportion of premature babies, are prone to complications, and have a high mortality and morbidity rate.